Caving mechanisms for a non-daylighting orebody - Banda, Sraj Umar (Luleå tekniska universitet, Geoteknologi, 2017)
The sublevel caving mining method is a mass production method with potentially very low operational costs. The success of this method is dependent on, among other factors, the cavability of the orebody and the overlying rock mass. However, caving of the surrounding rock mass also results in deformations in the cap rock as well as on the ground surface above the orebody being mined. From this follows that any existing infrastructure on the ground surface must be relocated as not to be affected by the mining-induced deformations.This thesis work was undertaken to bring about a better understanding of the rock mass behavior in the cap rock of non-daylighting orebodies, with particular application to the Printzsköld orebody as part of the LKAB Malmberget Mine. Rock testing, field observations and underground mapping was conducted to characterize the rock mass in the caving environment. A methodology for identifying the caving front based on seismic monitoring data was derived by studying the Fabian orebody (which has caved to surface), and using laser scanning data for validation. The methodology was then applied to the Printzsköld orebody to identify the caving front.Numerical modeling was performed for various scenarios of the rock mass as mining proceeded. Modeling included (i) stress analysis to understand stress changes and their effects on the rock mass behavior, (ii) discontinuum numerical modeling to quantify the influence of large-scale geological structures on the cave progression, and (iii) discontinuum cave modeling to simulate possible cave mechanisms in the cap rock more explicitly. Laser scanning together with seismic event data were used to calibrate the numerical models.The numerical simulation results showed that as mining progresses, the cap rock and hangingwall were exposed to stress changes that resulted in yielding. Two failure mechanisms were predominantly at play (i) shear failure (dominant in the cap rock) and (ii) tensile failure (dominant in the hangingwall). The presence of the ...